PENGARUH PELAKSANAAN PEMBELAJARAN DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X FASE E SMA NEGERI 9 KOTA JAMBI - Fitri Yanti; Lili Andriani (Universitas Batanghari Jambi, 2023)
This study aims to find out the influence of the implementation of learning and study habits on student learning outcomes in economics class X phase E of SMA Negeri 9 Jambi City. This type of research is research with a survey method with two independent variables and one dependent variable. The data collection technique in this study was by distributing questionnaires to research respondents. The data analysis technique in this study was multiple regression using the SPSS 16 program. The results showed that (1) The effect of the implementation of learning on learning outcomes obtained tcount > ttable (13.801 > 1.975). That is, the implementation of learning has a significant effect on student learning outcomes in economics class X class E phase of SMA Negeri 9 Jambi City, (2) The effect of study habits on learning outcomes is tcount > ttable (12.788 > 1.975). That is, study habits have a significant effect on student learning outcomes in economics class X phase E of SMA Negeri 9 Jambi City, (3) Implementation of learning and study habits have a significant effect on student learning outcomes in economics class X phase E of SMA Negeri 9 Jambi City. This is based on the value of Fcount> Ftable (103.099 > 3.06), so it can be concluded that HO is rejected. Keywords : Implementation of Learning, Habits, Learning Outcomes